1983
DOI: 10.1037/0021-9010.68.4.590
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of employment test validities by expert judgment.

Abstract: This study compares the relative accuracy of two methods of estimating employment test validity, (a) expert judgment and (b) small sample criterion-related validation studies The study was based on Navy data with samples of over 3,000 for each of nine jobs, with validity results on six tests for each job Twenty experienced psychologists estimated the observed validity for each of the 54 test-job combinations Both the random and systematic error in the expert judgments were evaluated Psychologists typically und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 7 publications
1
36
1
Order By: Relevance
“…Empirical correlations between predictors and job components require large sample sizes and performance ratings, so subject matter expert judgments may be collected instead (Scherbaum, 2005). For example, test experts or I‐O psychologists could estimate the validity coefficients between predictors and job components (Schmidt, Hunter, Croll, & McKenzie, 1983). Research suggests that expert judgments provide an accurate estimate of these relationships, at least for cognitive ability tests and with experienced judges (Hirsh, Schmidt, & Hunter, 1986; Schmidt et al, 1983).…”
Section: Description Of Synthetic Validationmentioning
confidence: 99%
“…Empirical correlations between predictors and job components require large sample sizes and performance ratings, so subject matter expert judgments may be collected instead (Scherbaum, 2005). For example, test experts or I‐O psychologists could estimate the validity coefficients between predictors and job components (Schmidt, Hunter, Croll, & McKenzie, 1983). Research suggests that expert judgments provide an accurate estimate of these relationships, at least for cognitive ability tests and with experienced judges (Hirsh, Schmidt, & Hunter, 1986; Schmidt et al, 1983).…”
Section: Description Of Synthetic Validationmentioning
confidence: 99%
“…The present study examined whether less experienced judges could also produce accurate estimates. Twenty-eight recent Ph.D.'s in 1/0 Psychology estimated observed validities for the same 54 job-test combinations used by Schmidt et al (1983). The estimates of these judges contained about twice as much random error as the experts' estimates.…”
mentioning
confidence: 91%
“…
In a previous study, Schmidt, Hunter, Croll and McKenzie (1983) demonstrated that estimates of the validity of cognitive tests made by highly trained and experienced judges are more accurate than empirical estimates obtained from small-sample validity studies. The present study examined whether less experienced judges could also produce accurate estimates.
…”
mentioning
confidence: 99%
“…This approach was suggested originally by the apparent success of judgments regarding the tasks reported by Krause (Krause & Woldstad, 1983;Smith et al, 1983). Recent reports of the success of expert estimations of test validity provide support for this approach (Schmidt, Hunter, Croll, & McKenzie, 1983). Estimates of computer-original validity have approached their theoretical, reliability set, limits for several tests on the APT System.…”
Section: Discussionmentioning
confidence: 99%